Antimicrobial activity of Byrsonima species (Malpighiaceae) - Michelin, Daniele C. [UNESP]; Sannomiya, Miriam [UNESP]; Figueiredo, Maria E. [UNESP]; Rinaldo, Daniel [UNESP]; Santos, Lourdes Campaner dos [UNESP]; Souza-Brito, Alba R. M.; Vilegas, Wagner [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Sociedade Brasileira de Farmacognosia, 2008)
Espécies de Byrsonima, família Malpighiaceae, são popularmente conhecidas como murici. Existem várias propriedades atribuídas às folhas de espécies de Byrsonima incluindo febrífuga, no tratamento de disfunções gastrintestinais e doenças de pele. Neste trabalho avaliamos a atividade antimicrobiana dos extratos das folhas de Byrsonima fagifolia, B. basiloba e B. intermedia usando o método de difusão em disco. Os resultados obtidos mostraram que os extratos metanólicos das folhas apresentaram atividade antimicrobiana contra todos os microrganismos testados.

Byrsonima species, family Malpighiaceae, is popularly known as murici. There are several properties attributed to the leaves of Byrsonima species including febrifuge, to treat gastrointestinal dysfunctions and skin diseases. In this work, the antimicrobial activity of Byrsonima fagifolia, B. basiloba and B. intermedia extracts obtained from the leaves were evaluated by using the disc-diffusion method. The results obtained showed that the methanol extracts of leaves had presented antimicrobial activity against all the microorganisms tested.
Atividade antimicrobiana de espécies de Byrsonima (Malpighiaceae)
Keywords: Malpighiaceae; Byrsonima; atividade antimicrobiana; Malpighiaceae; Byrsonima; antimicrobial activity